The Effect of Workload and Compensation on Employee Performance in the Expedition Department of CV. Apta Solusindo in Sidoarjo - Mega Cahyono Putera; Sulastri Irbayuni (PT Inovasi Pratama Internasional, 2023)
The purpose of this study is to explain the effect of workload and compensation on employee performance using the research object of CV Apta Solusindo in Sidoarjo. This study used a quantitative approach. The population in this study are employees of the expedition section of CV Apta Solusindo. While the sample in this study was 40 respondents in the CV Apta Solusindo expedition section in Sidoarjo. All tests using the SmartPLS Application show that all tests get values above the values that have been required for the test to be declared reliable. This study used quantitative research design, data analysis in the form of descriptive statistics and PLS analysis. The results showed that the workload was not able to drive the performance of CV employees. Apta Solusindo in Sidoarjo. Then the stimulus was able to encourage the performance of CV Apta Solusindo employees in Sidoarjo.